Gut-Brain Axis Impact on Canine Anxiety Disorders: New Challenges for Behavioral Veterinary Medicine - Carina Sacoor; John D. Marugg; Nuno R. Lima; Nuno Empadinhas; Liliana Montezinho (Veterinary Medicine International)
Anxiety disorders in dogs are ever-growing and represent an important concern in the veterinary behavior field. These disorders are often disregarded in veterinary clinical practice, negatively impacting the animal’s and owner’s quality of life. Moreover, these anxiety disorders can potentially result in the abandonment or euthanasia of dogs. Growing evidence shows that the gut microbiota is a central player in the gut-brain axis. A variety of microorganisms inhabit the intestines of dogs, which are essential in maintaining intestinal homeostasis. These microbes can impact mental health through several mechanisms, including metabolic, neural, endocrine, and immune-mediated pathways. The disruption of a balanced composition of resident commensal communities, or dysbiosis, is implicated in several pathological conditions, including mental disorders such as anxiety. Studies carried out in rodent models and humans demonstrate that the intestinal microbiota can influence mental health through these mechanisms, including anxiety disorders. Furthermore, novel therapeutic strategies using prebiotics and probiotics have been shown to ameliorate anxiety-related symptoms. However, regarding the canine veterinary behavior field, there is still a lack of insightful research on this topic. In this review, we explore the few but relevant studies performed on canine anxiety disorders. We agree that innovative bacterial therapeutical approaches for canine anxiety disorders will become a promising field of investigation and certainly pave the way for new approaches to these behavioral conditions.